2019
DOI: 10.9734/ijpss/2019/v29i230140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hexanal as a Post-harvest Treatment to Extend the Shelf-life of Banana Fruits (Musa acuminata var. Sweet Banana) in Kenya

Abstract: The short shelf-life of fruits in the tropics continues to be a pressing problem for farmers and other value chain actors. Hexanal is a naturally occurring compound that has received attention as a novel postharvest compound preservative. This study was conducted to determine the effect of hexanal on enhancing the postharvest shelf-life and quality of ‘sweet banana’ fruits. Two hexanal concentrations (2% and 3%) were applied as either a pre-harvest spray or a post-harvest dip. Fruits were obtained from two dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…reported similar results, where they found that control mango fruit showed higher respiration rate and ethylene synthesis than hexanal‐treated fruit during 35 days of storage. Lower respiration rate and ethylene synthesis in hexanal‐treated fruit as compared to control has also been described by many scientists in a variety of fruit, including apple, 39 mango 28 and banana 56 . However, contradictory results were also reported in many fruit, including tomato 23,37 and capsicum 24 …”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…reported similar results, where they found that control mango fruit showed higher respiration rate and ethylene synthesis than hexanal‐treated fruit during 35 days of storage. Lower respiration rate and ethylene synthesis in hexanal‐treated fruit as compared to control has also been described by many scientists in a variety of fruit, including apple, 39 mango 28 and banana 56 . However, contradictory results were also reported in many fruit, including tomato 23,37 and capsicum 24 …”
Section: Discussionmentioning
confidence: 71%
“…Lower respiration rate and ethylene synthesis in hexanal-treated fruit as compared to control has also been described by many scientists in a variety of fruit, including apple, 39 mango 28 and banana. 56 However, contradictory results were also reported in many fruit, including tomato 23,37 and capsicum. 24 Organic acids are considered the main substrates of the biogenesis of aromatic compounds, respiration and gluconeogenesis processes, and caused a decline in TA concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of three PLD genes was significantly down-regulated (Kumar et al, 2018). The shelf-life of bananas was extended by spraying them with 2%-3% hexanal on days 15 and 30 pre-harvest and dipping them in hexanal post-harvest (Yumbya et al, 2018). However, pre-harvest 2%-3% hexanal spray showed better fruit preservation (Yumbya et al, 2018).…”
Section: Hexanal Application In Enhancement Of Shelf-life Of Fruitmentioning
confidence: 99%
“…Fruit ripening and senescence have shown that the softening process is accompanied by the initiation of membrane damage, possibly involving phospholipase D (PLD). One of the recent, promising and innovative methods for fruit preservation is the use of hexanal [11,12]. Hexanal is a natural substance synthesised by plants via the lipoxygenase pathway after tissue damage or stress.…”
Section: Introductionmentioning
confidence: 99%